Derived equivalence classification of generalized multifold extensions of piecewise hereditary algebras of tree type - Asashiba, H.; Kimura, M. (Algebra and Discrete Mathematics, 2015)
We give a derived equivalence classification of algebras of the form Ă/〈∅〉 for some piecewise hereditary algebra A of tree type and some automorphism ∅ of Ă such that ∅(A⁽⁰⁾)=A⁽ⁿ⁾ for some positive integer n.